The midnight witch - Brackston, Paula (St. Martin's Press, 2014)
"When the sixth Duke of Radnor dies, his hapless son, Freddie, takes on his title, but it is his daughter, Lilith, who inherits his role as Head Witch of the Lazarus Coven. Raised as a witch, instructed in the art of necromancy, Lilith faces a daunting future, for the coven is threatened by a powerful group of sorcerers, the Sentinels. Nicholas Stricklend, a powerful force in the British government, is the Sentinel charged with wresting the Elixir from Lilith, and he cares not who he must crush in order to succeed. As a society beauty, engaged to another titled witch, and with a grieving mother and an unstable brother to look after, Lilith struggles to maintain her two very different existences. When she meets and falls in love with the talented artist Bram Cardale, she can no longer keep her life as a witch hidden, and she must choose between her loyalty to the coven, her duty to her family, and her love for Bram, or risk destroying everything she holds dear. Paula Brackston's debut novel, The Witch's Daughter, was the little book that could--with a captivating story, remarkable heroine, and eye-catching package, it has sold more than 130,000 copies in all formats. The Midnight Witch is another enchanting tale of love and magic, featuring her signature blend of gorgeous writing, a decadent and intriguing historical backdrop, and a headstrong and relatable heroine for which readers will cheer"--